Multiple Stimuli‐Responsive Supramolecular Hydrogels Constructed by Decamethylcucurbit[5]uril‐para‐phenylenediamine Exclusion Complex. Issue 21 (17th September 2021) - Guo, Hanling; Yang, Shengdu; Cao, Long; Chen, Lixia; Gao, Ruihan; Huang, Ying; Xue, Bai; Tao, Zhu
Abstract: The hydrogels composed of decamethylcucurbit[5]uril (Me10 Q[5]) and para ‐phenylenediamine ( p ‐PDA) are first reported herein. They are the first Q[5]‐based supramolecular hydrogels, the formation of which is driven by portal exclusion between Me10 Q[5] and p ‐PDA. The composition, structure, and properties of the Me10 Q[5]/ p ‐PDA‐based hydrogels are investigated by various techniques. Since the 1D supramolecular chain forms via portal exclusion between Me10 Q[5] and p ‐PDA is the key to the formation of the hydrogels, any competitive species, such as metal ions, organic molecules, and amino acids, which can affect the portal exclusion, can change the behavior of the Me10 Q[5]/ p ‐PDA‐based hydrogels. Hence, the hydrogels can be used for various applications. Importantly, the results may provide a new research direction for the preparation of Q[n]‐based hydrogels via portal exclusion of Q[n]s with guests. Abstract : In this work, the authors report a new kind of hydrogels constructed by Me10 Q[5] and p ‐PDA. Any species that could affect the exclusion interaction formed between Me10 Q[5] and p ‐PDA could change the behavior of the Me10 Q[5]/ p ‐PDA‐based hydrogels. Hence, the supramolecular hydrogels show a wide range of response functions.